Predictors of International Entrepreneurial Intention Among Young Adults: Social Cognitive Theory - Jannesari, Milad T. (Frontiers in Psychology, 2022)
This study investigated the psychological mechanism by which parents’ socioeconomic status, including income and social class, influences the international entrepreneurship intentions of young adults. This cross-sectional study investigated the international entrepreneurship intentions of young adults. Two datasets, self-reported (survey) and objective, were collected from 372 undergraduate students across 19 universities in China. Parents’ income and social class had a positive effect on international entrepreneurship intentions. Sense of power and motivational cultural intelligence played mediating roles in this relationship, and work experience moderated this relationship. The mediation tests revealed that sense of power and motivational cultural intelligence comprise a serial mediation process, in that order. The effect of motivational cultural intelligence on international entrepreneurship intentions was strengthened by young adults’ work experience. Future studies should assess the external validity of our proposed model by applying it to other segments of the population. We identified the underlying mechanism and moderator of the relationship between socioeconomic factors and international entrepreneurship intentions.